Comparative analysis of mineralocorticoid receptor antagonists and renin-angiotensin system inhibitors/angiotensin receptor neprilysin inhibitor in heart failure with mildly reduced ejection fraction - Lee, Chia-Chen; Te-Wei Kuan, David; Chang, Kai-Chun; Chen, Zheng-Wei; Cheng, Jen-Fang; Lin, Ting-Tse; Lin, Lian-Yu; Wu, Cho-Kai (Frontiers in Pharmacology, 2024)
Figure : 3 0.78-1.02) or HHF (hazard ratio = 1.01, 95% CI: 0.94-1.09). Conversely, RASI//ARNI use was linked to a lower risk of cardiovascular death (hazard ratio = 0.82, 95% CI: 0.71-0.94) but not HHF (hazard ratio = 0.995, 95% CI: 0.924-1.07).Landmark analysis showed no significant difference in outcomes for follow-up durations exceeding two years.MRA had a neutral effect on cardiovascular death and HHF, while RASI/ARNI was associated with a lower risk of cardiovascular death. RASI/ARNI may be more beneficial than MRA for HFmrEF patients. Regular re-evaluation is essential to adjust heart failure treatment.